Manajemen Pendidikan Islam dalam Tradisi Surau di Minangkabau - Aisa Haki Mayasa; Hasna ‘Izzatun Nawa; Intan Mulia Sari (Moral : Jurnal kajian Pendidikan Islam, 2026)
The surau is the oldest traditional Islamic educational institution in Minangkabau, with historical roots that trace back to the pre-Islamic era before evolving into a center of religious education, intellectual development, da’wah, and character formation. Beyond functioning as a place of worship, the surau also serves as a socio-cultural institution that preserves Islamic values and local traditions within Minangkabau society. This study aims to examine Islamic educational management within the surau tradition, with a focus on educational planning based on local philosophy, the leadership role of the Tuanku, and community-based supervision and financial management that support institutional sustainability. The research employs a qualitative method using a library research approach through the analysis of books, scholarly articles, and relevant documents. The findings show that educational planning in the surau is grounded in the philosophy of Adat Basandi Syara’, Syara’ Basandi Kitabullah (ABS-SBK) and the concept of Alam Takambang Jadi Guru, which integrate religious teachings, customary values, and life experiences into the learning process. Surau management is integrative, where the Tuanku acts as a charismatic leader, educator, manager, and moral role model. Its sustainability is supported by waqf, charitable contributions, and strong community participation. Despite modernization challenges, the surau remains relevant as a model of Islamic education that strengthens character, local wisdom, and cultural identity.